Cavernous Sinus Thrombosis in a Patient with aspirin-exacerbated respiratory disease: a case report - Lipska, Julia; Bocianiak, Bogumił; Hamerska, Laura; Hamerska, Julia; Antczak, Joanna; Fenrych, Urszula; Wojtczak, Karolina; Skupińska, Olga; Kajka, Anna (Quality in Sport, 2024)
Cavernous sinus thrombosis (CST) is a rare but life-threatening condition most commonly arising from trauma and paranasal sinus infections. The diagnosis of CST remains a formidable challenge despite advancements in medicine. Early identification and therapeutic intervention require an increased level of clinical awareness and a profound understanding of the pathophysiology of the disorder. This report presents a case of CST in a 58-year-old female with a long history of nasal and paranasal sinus polyposis and aspirin-induced asthma.